The Influence of Environmental Enrichment on Cardiovascular and Behavioral Responses to Social Stress. Issue 3 (April 2018) - Normann, Marigny C.; McNeal, Neal; Dagner, Ashley; Ihm, Elliott; Woodbury, Matthew; Grippo, Angela J.
ABSTRACT: Objective: Stress is linked to negative cardiovascular consequences and increases in depressive behaviors. Environmental enrichment (EE) involves exposure to novel items that provide physical and cognitive stimulation. EE has behavioral, cognitive, and neurobiological effects that may improve stress responses in humans and animal models. This study investigated the potential protective effects of EE on behavior and cardiovascular function in female prairie voles after a social stressor. Methods: Radiotelemetry transmitters were implanted into female prairie voles to measure heart rate (HR) and heart rate variability (HRV) throughout the study. All females were paired with a male partner for 5 days, followed by separation from their partner for 5 additional days, and a 10-day treatment period. Treatment consisted of continued isolation, isolation with EE, or re-pairing with the partner ( n = 9 per group). After treatment, animals were observed in the forced swim test (FST) for measures of stress coping behaviors. Results: Isolation elevated HR and reduced HRV relative to baseline for all groups ( p < .001). HR and HRV returned to baseline in the EE and re-paired groups, but not in the continued isolation group ( p < .001). Animals in the EE and re-paired groups displayed significantly lower immobility time ( p < .001) and HR ( p < .03) during the FST, with a shorter latency for HR to return to baseline levels after the FST, relative to the continued isolation group ( p < .001). Conclusions: EE and re-pairing reversed the negative behavioral and cardiovascular consequences associated with social isolation.